2019
DOI: 10.1021/acsomega.9b00731
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Removal of Multiple Heavy Metal Ions from River Water Using Ultrafine Mesoporous Magnetite Nanoparticles

Abstract: The exploration of simultaneous removal of co-existing or multiple pollutants from water by the means of nanomaterials paves a new avenue that is free from secondary pollution and inexpensive. In the aquatic environment, river water contains a mixture of ions, which can influence the adsorption process. In this respect, removing heavy metal ions becomes a true challenge. Here, four heavy metal ions, namely, Pb 2+ , Cd 2+ , Cu 2+ , and Ni … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(51 citation statements)
references
References 37 publications
0
49
0
Order By: Relevance
“…Hence, all the bimetallic material can be completely separated by magnetic attraction from the aqueous environment wherein it is dispersed. In the literature [26], ultrafine Fe 3 O 4 nanoparticles were employed to remove heavy metal ions from contaminated waters, thanks to their excellent adsorption performance. In a similar way, the magnetite nanoparticles obtained by laser ablation could act as adsorbents for the laser-ablated gold nanoparticles, forming a mixed bimetallic colloidal suspension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, all the bimetallic material can be completely separated by magnetic attraction from the aqueous environment wherein it is dispersed. In the literature [26], ultrafine Fe 3 O 4 nanoparticles were employed to remove heavy metal ions from contaminated waters, thanks to their excellent adsorption performance. In a similar way, the magnetite nanoparticles obtained by laser ablation could act as adsorbents for the laser-ablated gold nanoparticles, forming a mixed bimetallic colloidal suspension.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is possible to remove all the bimetallic material, including the possible load of adsorbed ligands, from the solvent and transport them thanks to the use of a magnetic field. In this regard, the presence of iron oxide gives the bimetallic colloid new possibilities for the adsorption of ligands, in addition to those inherent to gold nanoparticles, and also for removal of them from the aqueous environment, especially with regard to organic pollutants [25] and heavy metals [26]. Finally, our bimetallic colloids exhibit plasmonic properties, in addition to magnetic ones, due to the presence of gold nanoparticles, which allow application of the SERS technique for sensoristic purposes.…”
mentioning
confidence: 99%
“…Ultrafine magnetite nanoparticles (size range 4-17 nm) were generated through a co-precipitation reaction by Long et al [36] who then demonstrated the use of these nanoparticles for the removal of metal ions from river water. As part of the synthesis, surfactants were deliberately omitted.…”
Section: Single Magnetic Nanoparticle Materialsmentioning
confidence: 99%
“…However, there are still some disadvantages, such as low adsorption capacity, long adsorption time, but the main disadvantage is the complicated and costly removal of the used adsorbent after the adsorption process (filtration, centrifugation), which is not economically attractive [13,18,19]. It should be noted that only a few studies on the removal of heavy metals from the real environmental systems have been carried out with different adsorbents [20][21][22][23][24][25], whereas there is only one report on heavy metal removal from real sludge suspension using chitosan-based magnetic NPs [4].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies mainly focus only on metal removal from river water [20] or (industrial) wastewater [21,22] using magnetic nanoparticles, and the on use of nZVI-based adsorbents for metal removal from industrial metal-rich wastewater streams [23][24][25]. It…”
Section: Introductionmentioning
confidence: 99%